Antibacterial activity of peptides and bio-safety evaluation: in vitro and in vivo studies against bacterial and fungal pathogens - Mariadhas Valan Arasu; Naif Abdullah Al-Dhabi (Elsevier, 2023)
Background: Antimicrobial peptides are promising alternatives to antibiotics to treat bacterial and fungal infections, especially drug-resistant clinical pathogens. Methods: Antimicrobial peptides (AMPs) were synthesized and antimicrobial activity was assayed. The antibacterial mechanism, ATP production, ROS generation and molecular mechanism were determined. Biofilm inhibition assay was performed in planktonic bacterial cells and biofilm degradation assay was performed using mature biofilm. The synthesized AMP2 was subjected to in vitro and in vivo analysis to analyze the safety. Results: The synthesized peptides AMP1, AMP2, AMP3 and AMP4 exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria. The MIC values ranged from 1.5 ± 0.25-12.5 ± 1.25 µM and the MFC values range from 2.25 ± 0.12-25 ± 1.25 µM. F. solani showed fewer MFC values than other fungal strains. Time kill assay was performed and the AMP2 killed about 70 % of Acinetobacter baumannii at 1 × MIC concentration within 10 min incubation and killed 97 % of bacteria at 1 × MBC concentration within 15 min. The antimicrobial peptide AMP2 was highly effective against planktonic A. baumannii and L. monocytogenes. The tested AMP2 showed less toxicity to cell lines and Zebrafish. Conclusions: Antimicrobial peptides have potential antimicrobial properties against Gram-positive and Gram-negative bacteria. The in silico studies of these antimicrobial peptides are useful for eradicating drug-resistant bacteria.